Optimality Conditions for Semivectorial Bilevel Convex Optimal Control Problems - Bonnel, Henri; Morgan, J. (Springer New York LLC, 2013)
We present optimality conditions for bilevel optimal control problems where the upper level is a scalar optimal control problem to be solved by a leader and the lower level is a multiobjective convex optimal control problem to be solved by several followers acting in a cooperative way inside the greatest coalition and choosing amongst efficient optimal controls. We deal with the so-called optimistic case, when the followers are assumed to choose the best choice for the leader amongst their best responses, as well with the so-called pessimistic case, when the best response chosen by the followers can be the worst choice for the leader. This paper continues the research initiated in Bonnel (SIAM J. Control Optim. 50(6), 3224-3241, 2012) where existence results for these problems have been obtained. © Springer Science+Business Media New York 2013.